Notes on the occurrence of the tropical eel Anguilla bicolor bicolor in Peninsular Malaysia, Malaysia - Arai, Takaomi; Chino, Naoko; Zulkifli, Syaizwan Zahmir; Ismail, Ahmad (Wiley Blackwell, 2012)
Previous studies indicated that a tropical freshwater eel Anguilla bicolor bicolor occurs in Africa, India, Sri Lanka, Bangladesh, Myanmar, Indonesia and Australia, but an intensive survey has indicated an extended distribution range for the species into Peninsular Malaysia. Thus, A. b. bicolor is a native subspecies of Malaysia.